Fulfillment of the Rights of Children with Disabilities through the Involvement of Civil Society Organizations, Case of Yayasan Sayap Ibu - Handaningtias, Uliviana Restu; Indriyany, Ika Arinia; Ismalia, Lily (HK-Publishing, 2021)
AbstractThe rights of children with disabilities are still an unfinished discourse. In the big cities and remotes areas in Indonesia, sometimes we can hear cases of neglecting children with disabilities. The Indonesian government carries out various programs to eradicate cases of child neglect; one of the efforts taken is to permit social foundations that have special orphanages for children with disabilities to implement a legal adoption system. The question that then arises is, is the system sufficient to fulfill the rights of children with disabilities as mandated by Law No. 23 of 2002 on Child Protection? What components of rights were then successfully fulfilled through this adoption system, and what are the next steps for the government. This study seeks to provide an overview of how the adoption system fulfills children's rights with disabilities. This study using a qualitative method with a case study approach, the study's results photograph the reality experienced by foster children through the adoption system. The study results show that several main components as part of children's rights: the right to life, the right to grow without discrimination, the right to express opinions, and the right to get the best. Thus, from the results of this study, further research is needed to examine how the adoption system can be applied more effectively to reach the fulfillment of the rights of children with disabilities more optimally.Keywords Rights of children with disabilities, adoption system, social foundations for children with disabilitiesÂ AbstrakHak anak disabilitas masih menjadi wacana yang belum selesai. Kasus penelataran anak disabilitas masih terdengar baik di kota besar maupun di pelosok daerah di Indonesia. Pemerintah Indonesia melaksanakan beragam program untuk mengentaskan kasus penelantaran anak, salah satu upaya yang di tempuh adalah dengan memberikan ijin bagi yayasan sosial yang memiliki panti asuhan khusus anak disabilitas untuk menerapkan sistem adopsi secara legal. Pertanyaan yang kemudian timbul adalah, apakah sistem tersebut cukup untuk memenuhi hak anak disabilitas sebagaimana diamatkan oleh Undang-undang no 23 tahun 2002 tentang Perlindungan Anak? komponen hak apa sajakah yang kemudian berhasil dipenuhi melalui sistem adopsi ini dan bagaimana langkah pemerintah selanjutnya. Penelitian ini berusaha untuk memberikan gambaran mengenai bagaimana sistem adopsi memenuhi hak anak disabilitas. Menggunakan metode kualitatif dengan pendekatan studi kasus, hasil penelitian memotret realitas yang di alami oleh anak asuh melalui sistem adopsi tersebut. Hasil penelitian memperlihatkan beberapa komponen utama yang terpenuhi sebagai bagian dari hak anak, yaitu: hak hidup, hak tumbuh tanpa diskriminasi, hak menyampaikan pendapat, dan hak memperoleh yang terbaik. Dengan demikian, dari hasil penelitian ini dibutuhkan penelitian lanjutan untuk menelaah bagaimana sistem adopsi dapat diterapkan lebih efektif untuk menjangkau peneuhan hak anak disabilitas dengan lebih optimal.Â Kata kunci : hak anak disabilitas, sistem adopsi, yayasan anak disabilitas